The convergence of radiation and immunogenic cell death signaling pathways - Golden, Encouse; Pellicciotta, Ilenia; Demaria, Sandra; Barcellos-Hoff, Mary Helen; Formenti, Silvia C. (Frontiers in Oncology, 2012)
Ionizing radiation triggers programmed cell death in tumor cells through a variety of highly regulated processes. Radiation-induced tumor cell death has been studied extensively in vitro and is widely attributed to multiple distinct mechanisms, including apoptosis, necrosis, mitotic catastrophe, autophagy, and senescence, which may occur concurrently. When considering tumor cell death in the context of an organism, an emerging body of evidence suggests there is a reciprocal relationship in which radiation stimulates the immune system, which in turn contributes to tumor cell kill. As a result, traditional measurements of radiation-induced tumor cell death, in vitro, fail to represent the extent of clinically observed responses, including reductions in loco-regional failure rates and improvements in metastases free and overall survival. Hence, understanding the immunological responses to the type of radiation-induced cell death is critical. In this review, the mechanisms of radiation-induced tumor cell death are described, with particular focus on immunogenic cell death. Strategies combining radiotherapy with specific chemotherapies or immunotherapies capable of inducing a repertoire of cancer specific immunogens might potentiate tumor control not only by enhancing cell kill but also through the induction of a successful anti-tumor vaccination that improves patient survival.